Dengue infection triggered immune mediated necrotizing myopathy in children: a case report and literature review - Aphirak Mekmangkonthong; Jakkrit Amornvit; Numphung Numkarunarunrote; Montida Veeravigrom; Parichat Khaosut (BMC, 2022)
Abstract Background Immune-mediated necrotizing myopathy (IMNM) is a subgroup of idiopathic inflammatory myopathies manifesting with progressive weakness, elevated serum creatine kinase (CK) levels, and necrotizing myopathic features on muscle biopsy. There is a paucity of data on the clinical presentation of IMNM in children. We report a paediatric patient who developed anti-3-hydroxy-3-methylglutaryl-CoA reductase (anti-HMGCR)-positive necrotizing myopathy after recent dengue infection. Case presentation A previously healthy 9-year-old boy presented with acute proximal muscle weakness after recovery from dengue infection. Five days after the fever subsided, he could not stand from a squatting position. He denied having skin rash, arthritis, or other systemic features. He had marked elevation of CK level of 30,833 mg/dL and was put on steroid therapy. The patient initially responded to oral prednisolone, however the weakness persisted and muscle enzymes increased as steroids were decreased. He was then referred to our hospital for further assessment. Subsequent investigation revealed anti-HMGCR positivity along with specific histopathological findings consistent with IMNM. The patient was treated with six cycles of intravenous immunoglobulin (IVIG) monthly, then followed by a gradual taper of prednisolone and oral methotrexate weekly with complete recovery in motor power. Conclusions Our report presents a child with clinical manifestations of IMNM which can be categorized as acute onset of muscle weakness following dengue infection. Two key points supporting a diagnosis in this case are clinical response after immunosuppressive therapy and absence of rashes found in juvenile dermatomyositis.